2021
DOI: 10.1002/ccd.29589
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of two paclitaxel‐coated balloons for the treatment of in‐stent restenosis: The LONGTY ISR China randomized trial (LONGTY DCB vs. SeQuent Please DCB)

Abstract: Objectives: This study sought to compare the efficacy and clinical safety of the LONGTY drug-coated balloon (DCB) with those of SeQuent Please DCB in patients with in-stent restenosis (ISR).Background: Although DCB technologies have evolved, little is known about the clinical efficacy of the new-generation LONGTY DCB.Methods: This was a prospective, multicenter, randomized, noninferiority trial comparing LONGTY DCB with SeQuent Please DCB in patients with ISR. The primary endpoint was target lesion late lumen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The full description of included study characteristics is in Table 1 [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] ]. A total of 1767 (20.8%) patients received BA, 1088 (12.8%) VBT, 282 (3.3%) ROTA, 298 (3.5%) BMS, 1381 (16.3%) PCB, 25 (0.3%) SCB, 146 (1.7%) ZES, 761 (9.0%) EES, 1057 (12.5%) SES, and 842 (9.9%) PES (in 39 studies).…”
Section: Resultsmentioning
confidence: 99%
“…The full description of included study characteristics is in Table 1 [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] ]. A total of 1767 (20.8%) patients received BA, 1088 (12.8%) VBT, 282 (3.3%) ROTA, 298 (3.5%) BMS, 1381 (16.3%) PCB, 25 (0.3%) SCB, 146 (1.7%) ZES, 761 (9.0%) EES, 1057 (12.5%) SES, and 842 (9.9%) PES (in 39 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, DCB, a new choice for the treatment of coronary ISR, may compensate for many disadvantages of DES. Numerous clinical studies have confirmed that DCB plays a role in reducing ISR [17,18].…”
Section: Discussionmentioning
confidence: 96%